Tindak Verbal Abuse dalam Permainan mobile Legend di Indonesia: Kajian Sosiolinguistik - Almajid, Muhammad Rais (ESTETIK : Jurnal Bahasa Indonesia, 2019)
Mobile Legend is a game that is widely played by various groups from young to old. In communication, this game has provided a forum for communication in the form of chat or voice. But there are many found misuse of this communication space. Like players who often throw harsh words in the form of taunts / verbal swearings. The curses made by these fellow mobile legend players are of various types. The existence of this research is intended to find out how many types of verbal swearings are often spoken by mobile legend players in Indonesia. This study uses descriptive qualitative method, namely by collecting, analyzing and identifying verbal swear data. From this study found various types of verbal swearing which are classified into seven based on (1) animals, (2) professions, (3) limbs, (4) traits, (5) circumstances, (6) verbs, and (7) words object. The cursing cast by the player resulted in a decrease in the player's confidence in playing the Mobile Legend game well and caused the anger of the player who was hurled by hurtful swearings.